Endothelial Progenitor Cell Mobilization and Platelet Microparticle Release Are Influenced by Clopidogrel Plasma Levels in Stable Coronary Artery Disease - França, Carolina N.; Brunialti, Milena K.C.; Salomão, Reinaldo; Nucci, Gilberto de; Fonseca, Francisco A.H.; Bianco, Henrique T.; Barbosa, Simone P.; Izar, Maria C.O.; Kasmas, Soraia H.; Pinheiro, Luiz F.M. (Circulation Journal, 2012)
Background: Increased numbers of endothelial (EMP) and platelet (PMP) microparticles have been related to cardiovascular risk factors and coronary artery disease. Little is known about the early effects of statins and clopidogrel on these new biomarkers of vascular homeostasis. The aim of the present study was to evaluate pharmacokinetic interactions between atorvastatin and clopidogrel and their effects, alone or combined, on EMP, PMP, and endothelial progenitor cells (EPC). Methods and Results: A prospective open-label study enrolled subjects with stable coronary disease (n=26). Drugs were given daily for 3 weeks (atorvastatin 80mg, visits 1-3; clopidogrel 75mg, visits 2-4). Counts of EPC (CD34+/CD133+/KDR+), EMP (CD51+) and PMP (CD42+/CD31+), and pharmacokinetic parameters over 24h were assessed at each visit. Atorvastatin plasma concentrations were increased by concomitant therapy with clopidogrel (maximum serum concentration [Cmax], P=0.002; area under the clopidogrel or atorvastatin plasma concentration vs. time curve from 0 to the last detectable concentration [AUClast], P=0.03). After atorvastatin withdrawal there was an increase in clopidogrel plasma concentrations (Cmax, P=0.009; AUClast, P=0.039). PMP were inversely correlated with clopidogrel Cmax on visit 3 (rho=-0.57, P=0.006) and on visit 4 (rho=-0.54, P=0.01), and with clopidogrel AUClast on visit 3 (rho=-0.44, P=0.04), and on visit 4 (rho=-0.57, P=0.005). In addition, clopidogrel Cmax was correlated with EPC (CD133+/KDR+) on visit 4 (rho=0.48, P=0.025). No correlations of atorvastatin and MP or EPC were found. Conclusions: The balance between platelet MP release and EPC mobilization seems influenced by clopidogrel plasma levels, suggesting a protective mechanism on coronary artery disease. (Circ J 2012; 76: 729-736)